Legal protection for the minority shareholders in the holding company (a comparative study) (Journal of Misan Researches, 2021)
This research, which includes the legal protection of the minority shareholders in the holding company, deals with a very important issue, namely the legal protection of the minority shareholders in the subsidiary company of the holding companies, where the topic of the research is about the right of that minority in the subsidiary companies and we do not deal with organizational matters as a legal building for the holding company, but our topic is limited to protection The legal and judicial protection of the subsidiaries from the arbitrariness of the majority of the shareholders in the holding company, and we will shed light on the statement of the basic rights of the minority in the subsidiary of the holding company. The legislator, in one way or another, interferes with the provision of legal protection by acknowledging some of the rights represented in their right to be present in the General Assembly and the right to vote and debate on the decisions taken in addition to imposing responsibility on the members of the Board of Directors, whether it is a civil or penal liability. In addition to the legislative protection, there is judicial protection in which the judge had a major and important role in making the decision and obtaining it in the interest of the minority after it proved the harm against the perpetrator of the majority’s decision to offend and dispose of their decisions that were taken and harm the rights of others.